Productive and ecophysiological characteristics of some varieties of sulla (Hedysarum coronarium L.) in a Mediterranean area of Tuscany - Lombardi P.; Argenti G.; Sabatini S.; Pardini A. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
In areas with clayey soils of Central Italy a new interest in sulla (Hedysarum coronarium L.) is arisen. Different utilizations than the traditional haymaking of this forage crop are now possible. Two different ecotypes (the local 'Nugola' and 'Teramo' from Central Italy) and two Italian cultivars ('Grimaldi' and 'Sparacia') were compared in a coastal site near Livorno (Northern Tuscany). Data collection interested some productive and ecophysiological characteristics: DM and seed production, Leaf Area Index and sward structure. Results allowed a characterization of the four genotypes, providing also information on different management possibilities.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)